2020
DOI: 10.3389/fnins.2020.568813
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cerebrolysin on Hippocampal Neuronal Death After Pilocarpine-Induced Seizure

Abstract: Epilepsy is one of the most common and severe brain diseases. The exact cause of epilepsy is unclear. Epilepsy often occurs following brain damage, such as traumatic brain injury (TBI) and ischemia. Cerebrolysin is a porcine brain peptide that is a unique neurotropic and neuroprotective agent. Cerebrolysin has been reported to increase neuroprotective effects after TBI, ischemia, and other CNS diseases. However, the effects of cerebrolysin on seizures are not known. Therefore, this study aimed to investigate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 84 publications
1
12
0
Order By: Relevance
“…DeBoer 19 reported that poststroke CBL administration leads to recovery of motor function regardless rehabilitative training without a protective effect on stroke volume in a stroke model. In the seizure model, Kang 18 also confirmed that CBL can decrease hippocampal neuronal death after the seizure. In recent clinical studies, CBL can improve overall outcomes after moderate to severe traumatic brain injury patients 22 , 23 and was also safe, better for early rehabilitation patients after ischemic stroke 24 .…”
Section: Introductionmentioning
confidence: 76%
See 2 more Smart Citations
“…DeBoer 19 reported that poststroke CBL administration leads to recovery of motor function regardless rehabilitative training without a protective effect on stroke volume in a stroke model. In the seizure model, Kang 18 also confirmed that CBL can decrease hippocampal neuronal death after the seizure. In recent clinical studies, CBL can improve overall outcomes after moderate to severe traumatic brain injury patients 22 , 23 and was also safe, better for early rehabilitation patients after ischemic stroke 24 .…”
Section: Introductionmentioning
confidence: 76%
“…CBL is an intravenously administered small molecule peptide extracted from the porcine brain, composed of approximately 15% low molecular weight peptides and 85% amino acids in an aqueous solution and has been previously used as a nootropic drug 39 . It is a brain-specific pleiotropic agent that is proposed to target multiple pathways to improve functional recovery after neurological diseases and injuries in many central nervous system diseases [18][19][20][21][22] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lastly, to confirm the therapeutic action of sinomenine, we stained for NeuN, a specific marker of living neurons [ 37 ]. The results revealed that the number of active neurons in the spinal dorsal horn was lower in CCI rats than in control rats.…”
Section: Resultsmentioning
confidence: 99%
“…Cerebrolysin (EVER Neuro Pharma GmbH, Unterach am Attersee, Austria, 30 mL infusion), a unique neuropeptide preparation of low-molecular-weight neuropeptides (<10 kDa) and free amino acids, has been shown to have neuroprotective and neurorestorative properties [11,12]. Cerebrolysin has been reported to increase neuroprotective effects by protecting against excitotoxicity and oxidative stress as well as modulating the inflammatory response [34]. In addition, Cerebrolysin could enhances neurogenesis and neurorestoration through the activity of the neurotrophic factor and sonic hedgehog signaling pathways [35].…”
Section: Discussionmentioning
confidence: 99%